A Perceptive Journey through Postmodernism - Utpal Kumar Nandy; Shravani Nandy; Antara Nandy (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
"We live in a time of great uncertainty-caught in the transition from a bold and passionate optimism about the future to a deep skepticism and spirit of nihilism about finding any universal ways for mankind. We live in a 'Postmodern' time". This paper contains a descriptive note of the various phases, facets, ideas & ideologies behind the postmodern movement in art and architecture. It deals with the origin and evolution of the postmodernism. A contrast between its predecessor, modernism and postmodernism has been drawn to understand the underlying reasons triggering the change. The major characteristics defining postmodernism has been provided together with a brief mention of the major contemporary artists and their artworks.